Conditions de vie des Chrétiens sous le règne de l’Empire Ottoman au début du 19ème siècle - Ghazo, Mohamed Mahmoud (Al-Adab Journal, 2021)
This research aims to clarify the living conditions of the Christians in the early 19th century during the reign of the Ottoman Empire. The researcher tried to find out if the Eastern Christians were the only community living under hard circumstances and the causes behind that. To answer this question, this study limits itself to the Eastern Christian sects. The study analyzed the political influence of the West as well as the role which the Turkish governors played in these conditions from the point of view of Chateaubriand compared to that of other contemporary travelers to come up with a permanent conclusion. The findings showed that some Turkish governors abused the Eastern Christians for political, financial and religious reasons, where as it is evident that the Muslim people treated them with great respect and respected their freedom to practice their religious rituals.